EXPLORING STUDENTS’ PERCEPTION IN WRITING ACTIVITIES OF ENGLISH FOR BUSINESS USING LEARNENGLISH.BRITISHCOUNCIL.ORG - Ria, Tiara Nove (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2024)
The ability to write effectively in English for Specific Purposes (ESP) is a crucial skill for students aiming to engage in the global professional community. English for Business is a course designed to prepare students with workplace-ready English skills, emphasizing the importance of writing proficiency. To support writing skill development, incorporating innovative strategies such as utilizing websites as learning media is essential. This study focuses on students' perceptions of using the website learnenglish.britishcouncil.org as a tool to enhance their writing activities in English for Business. A descriptive qualitative method was adopted, involving 14 Management students from STIE Semarang as participants. The data were collected through semi-structured interview and document analysis. The findings showed that the use of the platform was has positive impact to the students. The students found it engaging, practical, and helpful in enhancing their writing performance. Students were satisfied with the interactive exercise, real world example and user-friendly platform, which supported their writing activities. This study underscores the potential of digital platforms like Learn English by British Council to facilitate effective learning experiences in ESP contexts and enhance students' readiness for professional communication.